If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + -1g) = 9g + 14 + -11g (7 * 2 + -1g * 2) = 9g + 14 + -11g (14 + -2g) = 9g + 14 + -11g Reorder the terms: 14 + -2g = 14 + 9g + -11g Combine like terms: 9g + -11g = -2g 14 + -2g = 14 + -2g Add '-14' to each side of the equation. 14 + -14 + -2g = 14 + -14 + -2g Combine like terms: 14 + -14 = 0 0 + -2g = 14 + -14 + -2g -2g = 14 + -14 + -2g Combine like terms: 14 + -14 = 0 -2g = 0 + -2g -2g = -2g Add '2g' to each side of the equation. -2g + 2g = -2g + 2g Combine like terms: -2g + 2g = 0 0 = -2g + 2g Combine like terms: -2g + 2g = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5m+4+6(6-2y)= | | 2x+9=x+62 | | x(x+6)=352 | | 7=4-2y | | x^4+4x+3=0 | | 6m+5-3m=7(m-1) | | (x-10)(x-5)=176 | | (8t^2-t-8)(4t^2+8t-1)= | | -12(x-12)=9(1+7x) | | 10z-4=2(5x-2) | | 6-4x=x-11x | | 3x+5x=12 | | 39X+55Y=12 | | (3x-4)(x^2-5x+6)= | | (-7x^9)(-3x^4)= | | 3s^2+10s-7+11s^2-8s+12+s-7= | | 9+3x=33 | | (1.80x+x)=(3.35x+x) | | (1.80+x)=(3.35+x) | | -9(y-6)=36 | | 4X+2Y=24 | | Y=.3(X-4)+4 | | 45(x+6)=35x-3 | | 6x-3x=4x-5 | | 3(5c-1)-2=13c+3 | | 7x+6y=8 | | 8-1.2c=2 | | -4k+2(5k-6)=-39 | | -2y-10=5y+18 | | X-7=2x-6 | | 9b+40=13d | | 4x-40=8 |